The development of service facilities in Fezzan and their impact on society during the monarchy 1952 – 1969 (Journal of Human Sciences, 2021)
Service facilities in Fezzan during the study stage are somewhat advanced in all fields, and this research paper aims to shed light on some of them and how they develop and their impact on society. Which dealt with education after independence, as well as the development in the education sector, vocational education, and social and recreational activities, As for the second axis, it studied the development of health services and their impact on society, as it was exposed to the health situation after independence, and how it developed later, and the curative services that were provided. And its impact on the lives of the population, and this research paper also contained a conclusion that included the most important findings of the researcher